2018
DOI: 10.1002/pro.3361
|View full text |Cite
|
Sign up to set email alerts
|

Lock and chop: A novel method for the generation of a PICK1 PDZ domain and piperidine‐based inhibitor co‐crystal structure

Abstract: The membrane protein interacting with kinase C1 (PICK1) plays a trafficking role in the internalization of neuron receptors such as the amino‐3‐hydroxyl‐5‐methyl‐4‐isoxazole‐propionate (AMPA) receptor. Reduction of surface AMPA type receptors on neurons reduces synaptic communication leading to cognitive impairment in progressive neurodegenerative diseases such as Alzheimer disease. The internalization of AMPA receptors is mediated by the PDZ domain of PICK1 which binds to the GluA2 subunit of AMPA receptors a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
27
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 25 publications
3
27
0
Order By: Relevance
“…PICK1 was originally cloned as a protein kinase Cα (PKCα) binding protein found in multiple tissues and organs, most abundantly in the brain, endocrine tissues, and skeletal muscle tissue (Human Proteome atlas). Through the PDZ domain, PICK1 interacts with a number of neurotransmitter receptors, transporters, and enzymes (Figure 7f), where in particular the interactions with the AMPAR [148][149][150][151][152][153][154][155][156][157] and the dopamine transporter (DAT) have received particular attention. Through the PDZ domain, PICK1 interacts with a number of neurotransmitter receptors, transporters, and enzymes (Figure 7f), where in particular the interactions with the AMPAR [148][149][150][151][152][153][154][155][156][157] and the dopamine transporter (DAT) have received particular attention.…”
Section: Targeting the Pdz Domain Of Protein Interacting With C Kinasementioning
confidence: 99%
See 2 more Smart Citations
“…PICK1 was originally cloned as a protein kinase Cα (PKCα) binding protein found in multiple tissues and organs, most abundantly in the brain, endocrine tissues, and skeletal muscle tissue (Human Proteome atlas). Through the PDZ domain, PICK1 interacts with a number of neurotransmitter receptors, transporters, and enzymes (Figure 7f), where in particular the interactions with the AMPAR [148][149][150][151][152][153][154][155][156][157] and the dopamine transporter (DAT) have received particular attention. Through the PDZ domain, PICK1 interacts with a number of neurotransmitter receptors, transporters, and enzymes (Figure 7f), where in particular the interactions with the AMPAR [148][149][150][151][152][153][154][155][156][157] and the dopamine transporter (DAT) have received particular attention.…”
Section: Targeting the Pdz Domain Of Protein Interacting With C Kinasementioning
confidence: 99%
“…Moreover, it was shown that FSC231 both inhibited co-immunoprecipitation of the GluA2 subunit of AMPARs in cultured hippocampal neurons, and influenced recycling of GluA2 after internalization. [148,149] BIO922 was described as identified through structure-based design and has a K i of 98 nm in blocking full length PICK1 and also a selectivity toward PICK1 versus PSD-95 and GRIP. In subsequent studies, an SAR study of FCS231 was performed, where a number of analogues were synthesized; however, only leading to a relatively modest improvement in affinity.…”
Section: Targeting the Pdz Domain Of Protein Interacting With C Kinasementioning
confidence: 99%
See 1 more Smart Citation
“…4A ) with the PDZ domain of PICK1. We crystallized the complex using a method of protein oxidation and carboxypeptidase treatment of the “tail-biting” dimer in the presence of 1o in a similar way as described 25 . The structure was solved using molecular replacement under standard procedures and the resulting structure was refined to an R factor of 15.5% and an Rfree of 17.7% to 1.69 Å resolution with good geometry (Supplemental Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…The appearance of the subpocket near R1 led us to consider additional optimization ideas for the R1 position, as we observed that both the CF3 of compound 1o and the pyrrolidine ring of the potent compound 1n 25 occupy the small subpocket described above. Docking studies suggested efficient entry into the subpocket could be enabled by introducing a meta -substituted aryl ring, and that a biaryl ring would optimize the stacking interaction with Phe53 when substituted directly adjacent to the ring junction (Supplemental Fig.…”
Section: Resultsmentioning
confidence: 99%